Venček domačih Predmeti, Slovencem sveti - Mlekuž, Jernej (ZRC SAZU, Založba ZRC, 2015)
A Medley of National Favourites. Things That Make Slovenes ShineSalted with the words of Benedict Anderson: to the Slovene nation, a love of Carniolan sausages, the Vače Situla, accordions and gibanica cakes "have an aura of fatality",Peppered with Raymond Williams: that Carniolan sausages, the Vače Situla, accordions and gibanica reproduce a "structure of national feeling", andServed with Karl Marx: these grandes dames of the Slovene nation weighas they must on the brains of living Slovenes.